Effects of Extracorporeal Shock Wave Therapy in The Maxillofacial Surgery Practice – A Systematic Review - Özkan, Enes; Özkan, Tuğba Haliloğlu (International Journal of Human and Health Sciences (IJHHS), 2019)
This review intends to provide researchers with a brief summary of extracorporeal Shock Wave Therapy (ESWT), and to bring new perspectives by systematic reviewing of the available data on the results of the various effects of ESWT regarding dentistry and the maxillofacial area. Literature search was conducted on December 2017 using the PubmedMedline, Google Scholar, Scopus and Web of Science databases.Articles between 1989 and 2018 were included.Search was performed using the keywords ‘alveolar, dentoalveolar, maxilla, mandibular, oral and sialolthiasis’ words in combination with ‘shock wave or shockwave’. The studies that were decided to include to this systematic review (n: 35) mostly consist of experimental and clinical studies. The current systematic review stated that ESWT has a success rate of up to 50% in the treatment of sialolithiasis. Shock wave therapy has also different dose-dependent effects on each tissue in the intraoral region. Shock wave parameters that will bring optimal biological effect to any treatment indication are yet to be clarified. International Journal of Human and Health Sciences Vol. 03 No. 04 October’19 Page : 186-195